Three stages of laboratory stewardship in improving appropriate Clostridioides difficile testing in a community-based setting - Michael S. Wang; Gretchen Zimmerman; Theresa Klein; Bethany Stibbe; Monica Rykse; Samuel Ballard; Naveen Vijayam; Joe Brown; Khateeb Raza; Shannon Beckman; Andrew M. Skinner (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract